Battle of Mohacs 1526 and its impact on the geopolitical situation in Central and Eastern Europe - Andrusyak, Yaroslav; Tovtyn, Yana (Before the Battle, 2023)
The problem of Turkish expansion, in the context of which the Battle of Mohacs is considered, is very relevant among researchers. Events of the first third of the 16th century radically changed the historical development of the region of Central-Eastern Europe, and this change was directly related to the defeat at the Battle of Mohacs on August 29, 1526. The date of the battle became a chronological border in the history of the Hungarian, Czech Kingdom and adjacent territories (Slovakia, Croatia and others). The unsuccessful internal policy of the representatives of the Czech-Hungarian line of the Jagiellonian dynasty led to a loss of support among the Czech szlachta and Hungarian magnates. It was not possible to attract the advanced monarchs of Europe to the fight against Turkish aggression. The Hungarian and Czech estates underestimated the level of danger and cared more about their own political and economic interests (The unsuccessful policy of the representatives of the Czech and Hungarian Jagiellon dynasty led to the loss of the support among the Czech lords, Hungarian magnates). All this led to the „Mohacs catastrophe”, where the flower of the Hungarian nobility died. According to various statistics, the royal army numbered 25–28 thousand (of which 8 thousand foreigners: Czechs, Poles, Croats, Serbs, Germans, Italians, Spaniards) soldiers and 53–80 guns. The number of Turkish troops was 55–65 thousand soldiers and 160 guns. The defeat at Mohacs had serious geopolitical consequences. Thus, the majority of the Hungarian small and middle gentry supported Janos Zapolyai, and representatives of the higher gentry supported Ferdinand I of Habsburg, who was also elected to the Czech throne. The Transylvanian principality appeared (depended on Turkey), and the so-called Royal Hungary arose on the other part of Hungary. Thus, the Turkish Empire established hegemony in the central-eastern region of Europe.